Kepastian Hukum Bagi Persekutuan Komanditer Dalam Kepemilikan Hak Atas Tanah Menggunakan Nama Sekutunya - Dias Artania Jaya; M. Sudirman; Erny Kencanawati (Jurnal Nuansa Kenotariatan, 2020)
Commanditaire Vennootschaap is one of business entity which mostly used by small and medium enterpreneurs. Until now, CV is till considered as a nonlegal entity, even though CV has the requirements to become a legal entity. In conducting its daily activities, CV require land and building, in addition the land and building’s right can be used as collateral for loan performed by CV. At present, CV can not have land right, because Agrarian Law has not regulate ownership of land right for non-legal entity. Hence, CV has land right using their partner name. The method used in this research is a juridical normative research method supported by juridical empirical method. The approach focuses on the study of primary legal materials in the form of laws and regulations, namely the legislation of Code of Commercial Law, Civil Code, Agrarian Law, as well as court decree. Based on the results of this research, it was concluded that ownership of land right using partner name can not be considered as ownership of land right of CV, because partner CV and CV have separate wealth and separate tax subject, also can cause legal consequenses which detrimental to CV and its partners. Whereas the Circular of Granting HGB for CV issued by BPN actually Circular of Granting HGB for CV’s partners apparently did not provide legal certainty because it does not explain the procedures and the legal consequences. To obtain legal protection, CV and its partners can give contention to the government to clarify the status, right and obligation of CV or to clarify the Circular granting HGB to CV’s partners in a statutory regulation